2017
DOI: 10.1039/c7ra02271a
|View full text |Cite
|
Sign up to set email alerts
|

Scaling the effect of hydrophobic chain length on gene transfer properties of di-alkyl, di-hydroxy ethylammonium chloride based cationic amphiphiles

Abstract: Asymmetric hydrocarbon chains influence the efficiency of cationic lipids based liposomes in nucleic acid delivery. A systematic investigation of role of asymmetry in transfection efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…Liposomes are composed of DODEAC (N,N-di-n-octadecyl-N,N-dihydroxyethylammonium chloride), a well-known cationic lipid, and prepared by the injection method. 20,21 MVs were collected from the MCF-7 cell media using differential centrifugation. The fusion process was validated via a FRET-based lipid-mixing assay (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liposomes are composed of DODEAC (N,N-di-n-octadecyl-N,N-dihydroxyethylammonium chloride), a well-known cationic lipid, and prepared by the injection method. 20,21 MVs were collected from the MCF-7 cell media using differential centrifugation. The fusion process was validated via a FRET-based lipid-mixing assay (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…There are similar reports available in the literature on hybrid-vesicle preparation by fusing EVs with synthetic liposomes with PEG. , Importantly, in this work, the mechanical aspects of these hybrid vesicles in various PEG% are determined by a FRET-based lipid-mixing assay, which is a completely new feature and has an impact on the hybrid vesicle’s delivery efficacy. Earlier we showed that asymmetric lipid-based vesicles are promising carriers, and their delivery efficiency depends on the structural flexibility/rigidity balance. Taking note of these factors, to improve the delivery efficacy of a synthetic liposome further, in this work we fused asymmetric liposomes with MVs (derived from breast cancer MCF-7 cells) with polyethylene glycol (PEG) as a fusogenic agent and developed a hybrid vesicle system. We validated hybrid-vesicle formation with FRET and flow cytometry-based analysis and used them for model siRNA (Alexa647 tagged) delivery into MCF-7 cells to check the performances of these newly developed carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that the symmetry of the two alkyl chains bound to the headgroup plays some role in the behavior of two-tailed cationic lipids (Chandrashekhar et al, 2011;Hiwale et al, 2017;Le Corre et al, 2014;Wang and Macdonald, 2004). SAR studies revealed that the degree of asymmetry between the two tails strongly impacts the phase behavior of the resulting lipid as a consequence of the differences in the overall tail free volume (Zhang et al, 2011).…”
Section: Aliphatic Chainsmentioning
confidence: 99%
“…The CA structure significantly affects the efficiency of NA delivery to eukaryotic cells. In recent years, many monocationic amphiphiles have been obtained [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] that form liposomes for NA delivery. In this review, we will consider polycationic amphiphiles, which, compared to monocationic analogs, enable the more efficient transport of NAs into cells due to the formation of a system of distributed charges in the polyamine matrix and their ability to facilitate NA release from endosomes.…”
Section: Introductionmentioning
confidence: 99%